UZBEKISTAN - A NEW STAGE IN THE BUILDING OF A DEMOCRATIC STATE - Dilrabo Chorieva (Web of Journals Publishing, 2025)
This article analyzes the norms of the Revised Constitution and its implementation mechanisms, the role of the mixed electoral system, the emergence of new forms of democracy as a result of the participation of political parties in elections, the fact that more than half of the voters are women, increasing the socio-political activity of women, ensuring and protecting their rights and interests, activating their participation in socio-political reforms, ensuring their active participation in every aspect of society, and the fact that as a result of such opportunities, the number and share of women in the parliament and local councils of our country are increasing, and issues related to the principles of building a social state.
Keywords: Democracy, mixed electoral system, changes in the electoral legislation of Uzbekistan, political parties, women, local councils, senate, Oliy Majlis, social state, democratic state, Third Renaissance.